The body as interface between theoretical and practical law in Fichte’s theory of 1796/1797 - Arrese Igor, Héctor Oscar (Estudios de Filosofía, 2014)
In this paper, I try to test the consistency of the chtean theory of the natural right. I do this by comparing the kind of intersubjectivity that the body implies to that which can be deduced from the theory of the state, as it is based on the moral-psychological presupposition of the universal egoism.